ECG Quiz no. 27 - Okreglicki, A. (SA Heart Journal, 2017)
A 56-year-old woman with a past history of hypertension and a stroke 2 years ago, currently only on a thiazide, attended a peripheral hospital clinic complaining of lethargy and dizziness for the past 2 weeks. An ECG was done and sent through for an opinion regarding management.